2016
DOI: 10.1097/hcr.0000000000000152
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Anxiety and Depression in Patients With Takotsubo Stress Cardiomyopathy to Those With Acute Coronary Syndrome

Abstract: In comparison with a control group with ACS, patients who presented with TSCM have higher levels of anxiety but not depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 36 publications
2
26
2
Order By: Relevance
“…Our data do not appear to confirm the association between Tako-tsubo and anxious syndromes previously reported in literature [10, 12, 23]. …”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our data do not appear to confirm the association between Tako-tsubo and anxious syndromes previously reported in literature [10, 12, 23]. …”
Section: Discussioncontrasting
confidence: 99%
“…However, the diagnosis was based on clinical records and therefore, not verified through semi-structured interviews, which is recognized as the method most capable to producing reliable diagnoses in psychiatry. Other surveys adopted screening by brief structured clinical interviews [10], questionnaires [11], or rating scales [12] but this is the first study to the best of our knowledge that used a more complex methodology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found a greater impact of Post-Traumatic Stress Disorder (PTSD) after discharge (Salmoirago-Blotcher et al, 2016) in TTS compared to patients with myocardial infarction or healthy controls. Of interest, the time elapsing between the cardiac event and the psychological assessment was extremely variable, ranging from hours (Delmas et al, 2013) to years (Goh et al, 2016).…”
Section: Life-events and Psychological Traumamentioning
confidence: 99%
“…The authors found that TCM patients had higher levels of chronic anxiety, but not chronic depression, in comparison with ACS patients. After a multivariable adjustment, chronic anxiety but not chronic depression was associated with TCM, and a history of chronic anxiety was associated with TCM status with an emotional trigger 20 . This implies that clinicians should focus on patients with chronic anxiety and a recent emotional trigger with respect to diagnosis and management of TCM.…”
mentioning
confidence: 99%